Closing Speech - Between Theory and Practice - Kowalczyk-Ludzia, Marta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The development of rhetoric in criminal procedure is reflected in every court trial. The right of the parties to present their final speech before the court (Article 406 of the Pol-ish Code of Criminal Procedure) is important for achieving the required verdict. This paper tries to answer the question about the actual extent to which the said regulation is used by the parties to achieve their objectives. The deliberations are based on an analysis of the results of research conducted by the author.